INFLUENCE OF HYDROXYPROPIL METHYLCELULLOSEAND PECTIN MATRIX ON THE SOLUBILITY PROFILE AND CRYSTAL STABILITY OF THEOPHYLLINE - Yoga W. Wardhana; Mulyadi G. Tedjasaputra (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2011)
INFLUENCE OF HYDROXYPROPIL METHYLCELULLOSEAND PECTIN MATRIX ON THE SOLUBILITY PROFILE AND CRYSTAL STABILITY OF THEOPHYLLINE. Humidity is one of a factor affecting drug stability. Theophylline is a good sample which easily modified by humidity. In this study, we investigate the effect of polymer matrix of hidroxypropyl methylcelullose (HPMC) and pectin to inhibit the humidity-caused crystal stability changes of theophylline. Theophylline anhydrous (Ta) and mixture of Ta and matrix (80 : 20, 70 : 30 and 60 : 40) were used as the object of the study. The mixture was pressed to tablets using a Single Punch 12 mm flat E. Korsch machine. Humidity exposure was performed using a desiccator in room temperature (27 oC), with 94 % of relative humidity for 3 weeks of storage. The ability of matrix in inhibiting the change of Ta to theophylline monohydrate (Tm) was determined by comparing the result of dissolution test and X-Ray diffraction patterns from material test before and after humidity exposure. The results suggest that both polymers inhibited the changes of Ta to Tm. However, pectin was more superior than HPMC in inhibiting the hydration.